Human Histology of a New Bulking Agent Containing PMMA-Microspheres for Gastric Reflux and Urinary or Fecal Incontinence - Lemperle, MD, PhD, Gottfried (International Journal of Innovative Research in Medical Science, 2022)
Background and study design: Bulking agents are currently not available for the treatment of gastroesophageal reflux disease (GERD) and only play a secondary role in the treatment of stress urinary incontinence (SUI) and fecal incontinence (FI). The main reasons for their reluctant use are a relatively high rate of reported adverse events with currently approved materials and competitive technologies. Microspheres made from polymethyl-methacrylate (PMMA) have been successfully injected as dermal fillers for 30 years. They produce a soft and pliable "living implant", do not dislocate, and meet all characteristics of an ‘ideal’ injectable bulking agent. Methods: To examine the histological responses to 125µm PMMA microspheres, 28 different blebs were injected subcutaneously into a human forearm and excised after 1 week, and 1, 6, and 12 months. Results: At 1 month, most spheres were engulfed by a large number of macrophages, which later merged into one giant cell embracing each individual microsphere. At 1 year, most macrophages had left the implant, whose wide interspaces were filled with capillaries and collagen fibers. Monophasic highly cross-linked hyaluronic acid (HA) generates about 65% tissue. In comparison, biphasic HA, which does not keep the heavier PMMA microspheres in suspension, generates around 50% tissue, similar to the carrier material atelo-collagen (AC). Conclusions: PMMA microspheres produce a soft, fully vascularized “living implant”, which is resistant to erosion, migration, and dislocation. The most effective available carrier appears to be monophasic HA-gel, which keeps the beads apart and allows tissue in-growth at about 65% of the total implant volume.